Bone Mineral Analogue Ceramic Block as an Instant Adhesive to Biological Soft Tissue. Issue 6 (8th February 2021) - Sugiura, Yuki; Okada, Masahiro; Hirano, Ken; Matsumoto, Takuya
Abstract: The disadvantages of surgical sutures, such as secondary tissue damage, surgical site infection, and liquid leaking, can be reduced by biological soft‐tissue adhesives. Although non‐bioresorbable bone substitute materials sufficiently adhere to soft tissues, enabling immobilization of implantable devices, their non‐bioresorbable property limits their clinical use. This study reports the excellent adhesion properties of octacalcium phosphate (OCP), a bioresorbable mineral analogue of immature bone. Blocks of OCP strongly adhere to mouse dermal tissues, enhancing their protein adsorption capacity as demonstrated in ex vivo shear adhesion tests. When soaked in antibacterial solution, the OCP blocks easily adsorb the antibacterial agents in their internal nano‐pores and on their surfaces, imbuing them with antibacterial ability. Therefore, the OCP blocks are a solid‐state material with strong adherence to biological soft tissues and, are especially promising for detachable body‐implantable and/or external devices. Abstract : Owing to disadvantages of surgical sutures, newly instant soft tissues adhesives are attractive. Octacalcium phosphate (OCP) is an analogue of bone minerals; the blocks strongly adhered to mouse dermal tissues. The adhesive strength of OCP blocks far exceeded that of commercial fibrin glue. Furthermore, when OCP blocks are soaked in antibacterial solution, the OCP blocks easily exhibit antibacterial ability.